ANALISIS NET PROFIT MARGIN (STUDI KASUS UD.BERKAH ILAHI TAHUNAN JEPARA) Hamdi Sari Maryoni1),& Wenny Djuari 2) 1Fakultas Ekonomi, Universitas Pasir Pengaraian email: hamdiyoni@yahoo.co.id 2Fakultas Ekonomi, Universitas Putra Indonesia Cianjur email: wenny - Hamdi Sari Maryoni , Wenny Djuari (Jurnal Ilmiah Cano Ekonomos, 2016)
This study with the aim to find out how much profit is generated by Divine UD. Berkah to analyze the development of future business to be more effective and efficient. Net Profit Margin analysis used in this study to assess the achievements of the business activities of UD.Berkah Divine. Net Profit Margin Analysis is part of one of the profitability ratios in financial valuations in seeing the growth or development of the profit dihasilakan in analyzing financial statements. Types and data collection were used in this research is secondary data from the sales and operating profit have been processed from UD Divine Blessing. Collecting data with engineering documentation, that data have been taken from the Divine UD. Berkah used on the production of income. The conclusion from this study that during one year, the work done by the Divine UD.Berkah in January represents operating income was best achieved by Rp.15,786,000, followed in December 2015, amounting Rp.14,050,000, and profits followed in June 2015 amounting Rp.13,335,000. Income from operations experienced a very significant decline and the lowest month of October 2015 is Rp. 8,250,850. Furthermore, the sales achieved by the best Divine UD.Berkah happened the last few weeks in December 2015 in the amount of Rp. 111,145,150 or the percentage of net profit margin of 12.64%. Sales decreased by a data table 1 occurred in October 2015 amounted Rp.101,234,000 or 8.15% from other months by 2015.